The State and the Rise of a Continuous Popular Educational Sphere in Sweden c. 1870s–1910s - Berg, Anne (Nordic Journal of Educational History, 2015)
The age of imperialism, from the 1870s to the 1910s, saw the rise of a popular educational sphere in Sweden as well as in the rest of Europe. This sphere was characterised by an incomparable institutional growth and continuity. In earlier research, the growth of popular education has often been explained as a consequence of class-politics and the formation of a civil society. In this article I argue that another explanatory factor needs to be inserted in the overall historical narrative in Sweden, namely the material pre-conditions of the organisations that rose to stability and especially the economic grants offered by the industrial state. In fact, this study shows how the growth of the sphere and state grants to institutions such as folk high schools and lecture-societies went hand in hand. Furthermore it is shown how the share of public funding from the central bureaucracy as well as the local institutions of government successively became the dominant sources of income for folk high schools and lecture-societies. Thus, the article argues that the economic role of the state was a crucial factor for the rise of a continuous popular educational sphere.